2014
DOI: 10.1007/s10620-014-3043-4
|View full text |Cite
|
Sign up to set email alerts
|

Significant Variation in Recommendation of Care for Women of Reproductive Age with Ulcerative Colitis Postileal Pouch–Anal Anastomosis

Abstract: There is significant intra- and inter-group variation in management of women post-IPAA. There is need for consensus among subspecialists involved in managing women with this complex condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…41 The standard indications for a caesarean section for women with IBD, aside from obstetric indications, are active perianal disease and previous pouch surgery; however, there may be significant variation between clinicians in recommendations of care for women of reproductive age with UC and an ileo-pouch anastomosis. 42 An association between birth by caesarean section and an increase in subsequent development of IBD particularly in childhood and young adulthood, has previously been reported, 43 so caesarean section for nonobstetric or nongastrointestinal indications should be carefully considered. Multidisciplinary discussion involving colorectal surgery, gastroenterology and obstetrics to determine the optimal mode of birth for an individual woman is recommended.…”
Section: Discussionmentioning
confidence: 98%
“…41 The standard indications for a caesarean section for women with IBD, aside from obstetric indications, are active perianal disease and previous pouch surgery; however, there may be significant variation between clinicians in recommendations of care for women of reproductive age with UC and an ileo-pouch anastomosis. 42 An association between birth by caesarean section and an increase in subsequent development of IBD particularly in childhood and young adulthood, has previously been reported, 43 so caesarean section for nonobstetric or nongastrointestinal indications should be carefully considered. Multidisciplinary discussion involving colorectal surgery, gastroenterology and obstetrics to determine the optimal mode of birth for an individual woman is recommended.…”
Section: Discussionmentioning
confidence: 98%
“…Delivery decisions in women with IPAA are complex, and women frequently receive conflicting advice from various specialists, 136 which partly reflects the inconclusive data in the literature. During pregnancy, women with IPAA may experience an increased stool frequency which returns to baseline 3 months post-partum, irrespective of delivery modality.…”
Section: Management Of Ibd During Pregnancymentioning
confidence: 99%
“…A study conducted by Cornish et al demonstrated that women with UC have a cesarean section rate compared with the general population unlike women with CD, who are more prone to undergo C-sections [13]. Bradford et al illustrate that C-sections remains more prevalent among women with IBD, most likely due to peri-anal disease, in addition to the other obstetric complications [26]. According to the European Crohn's and Colitis Organization, C-section remains a mandate in women who develop the active perianal disease during pregnancy, owing to the increased risk of complications to both the mother and the child.…”
Section: Reviewmentioning
confidence: 99%
“…Methotrexate: Methotrexate acts by Inhibiting enzymes in the metabolic pathway of folic acid interfering in purine and pyrimidine synthesis [26], making it devastating for both the mother and the fetus. The drug is categorized as FDA class X.…”
Section: Reviewmentioning
confidence: 99%